Evaluasi Rasionalitas Penggunaan Antihipertensi di Puskesmas Jagakarsa, Jakarta Selatan Periode Juli-Desember 2023 - Hasanah, Kurniatul; Siswati, Siswati; Adriyati, Nur Azmi (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2025)
Hypertension is defined as a condition where an individual's systolic blood pressure is consistently above 140 mmHg and diastolic blood pressure is above 90 mmHg, as determined by two separate measurements. This condition represents a major public health challenge, with high rates of morbidity and mortality globally, particularly in Indonesia. The World Health Organization (WHO) estimates that 50% of all drugs worldwide are prescribed, dispensed, or sold inappropriately. This often leads to improper drug use by patients, resulting in adverse clinical and economic consequences. This can cause unwanted problems such as unachieved therapeutic goals and increased side effects of drugs. The purpose of this study was to determine the demographics of hypertensive patients, the characteristics of hypertensive patients, patterns of antihypertensive use and the rationality of antihypertensive use including appropriate indications, appropriate drugs and appropriate doses. This study was an observational retrospective study using a descriptive analysis design. The sample used was 166 patients who met the inclusion criteria. The results showed patient demographic data for female gender as many as 89 patients (53.62%) and male as many as 77 patients (46.39%). Based on age, the majority of patients were in the range of 46-55 years, as many as 51 people (30.72%). Based on disease characteristics, the majority of patients were in stage II hypertension, as many as 113 patients (68.07%). Based on complications or comorbidities, the majority of patients were hypertensive patients without complications and comorbidities, as many as 69 patients (41.57%). The most frequent use of antihypertensives was in the form of single therapy, as many as 146 patients (87.85%), namely the calcium channel blocker (amlodipine) drug group, as many as 139 patients (83.73%). The results of the evaluation of the rationality of antihypertensive use in the category of appropriate indications were 100% (166 patients), appropriate drugs were 100% (166 patients) and appropriate doses were 94.58% (157 patients). All samples examined demonstrated adherence to the principles of rational antihypertensive therapy, specifically regarding appropriate indications and drug selection. The aspect of appropriate doses reached 94.58%.